Whipple's disease mimicking rheumatoid arthritis can cause misdiagnosis and treatment failure - Glaser, Cornelia; Rieg, Siegbert; Wiech, Thorsten; Scholz, Christine; Endres, Dominique; Stich, Oliver; Hasselblatt, Peter; Geißdörfer, Walter; Bogdan, Christian; Serr, Annerose; Haecker, Georg; Voll, Reinhard E.; et al. (Orphanet Journal of Rare Diseases, 2017)
Whipple's disease, a rare chronic infectious disorder caused by Tropheryma whipplei, may present with predominant joint manifestations mimicking rheumatoid arthritis (RA).A retrospective single-center cohort study of seven patients was performed. Clinical symptoms were assessed by review of medical charts and Whipple's disease was diagnosed by periodic-acid-Schiff-stain and/or Tropheryma whipplei-specific polymerase-chain-reaction.Median age at disease onset was 54 years, six patients were male. Median time to diagnosis was 5 years. All patients presented with polyarthritis with a predominantly symmetric pattern. Three had erosive arthritis. Affected joints were: wrists (5/7), metacarpophalangeal joints (MCPs) (5/7), knees (5/7), proximal interphalangeal joints (PIPs) (3/7), hips (2/7), elbow (2/7), shoulder (2/7). All patients had increased C-reactive-protein concentrations, while rheumatoid factor and anti-CCP-antibodies were absent, and were initially (mis)classified as RA-patients according to EULAR/ACR-criteria (median DAS28 4.3). Six patients received antirheumatic treatment consisting of prednisone with methotrexate and/or leflunomide, three were additionally treated with at least one biologic agent (abatacept, adalimumab, etanercept, rituximab, tocilizumab). Most patients showed insufficient treatment response. In all patients Tropheryma whipplei was detected in synovial fluid by polymerase-chain-reaction; in three patients the diagnosis of Whipple's disease was further ascertained by periodic-acid-Schiff-staining. Gastrointestinal symptoms and other extra-articular manifestations were absent, mild or non-specific. Treatment was initiated with trimethoprin/sulfamethoxazole in five and doxycycline/hydroxychloroquine in two patients and had to be adapted in five patients. Finally, all patients had good treatment responses with improvement of arthritis and extra-articular manifestations.Whipple's disease is rare and can mimic rheumatoid arthritis. Especially patients with seronegative rheumatoid arthritis with a prolonged disease course and insufficient treatment response should be reevaluated for Whipple's disease.
EVALuna2:7750